MITOLOGI SUKSESI PEREMPUAN DALAM IKLAN NIVEA VERSI “NEVER STOP CARING” - Herly Hutahaean; Lasmery RM Girsang (Universitas Bunda Mulia, 2019)
ABSTRACTThere are many kinds of functions of advertising; one of them can be used for campaigning human care. As represented through